Fluoroquinolone resistant mechanisms in methicillin-resistant Staphylococcus aureus clinical isolates in Cairo, Egypt - Hashem, Rasha A; Yassin, Aymen S; Zedan, Hamdallah H; Amin, Magdy A (The Journal of Infection in Developing Countries, 2013)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a persistent problem in community and health care settings. Fluoroquinolones are among the drugs of choice used to treat MRSA infections. This study aims to identify different mechanisms of fluoroquinolne resistance in local MRSA random sampling isolates in Cairo, Egypt. Methodology: A total of 94 clinical isolates of S. aureus were collected from two major University hospitals in Cairo. Identification was confirmed by appropriate morphological, cultural, and biochemical tests. The antibiotic susceptibility pattern was determined for all isolates. The possible involvement of efflux pumps in mediating fluoroquinolone resistance as well as changes in the quinolone resistance determining region (QRDR) of gyrA and gyrB genes were investigated Results: A total of 45 isolates were found to be MRSA, among which 26 isolates were found to be fluoroquinolone-resistant. The MIC values of the tested fluoroquinolones in the presence of the efflux pump inhibitors omeprazole and piperine were reduced. Measuring the uptake of ciprofloxacin upon the addition of the efflux pump inhibitor omeprazole, an increased level of accumulation was observed. Non-synonymous and silent mutations were detected in the QRDR of gyrA and gyrB genes. Conclusions: These results shed light on some of the resistance patterns of MRSA strains isolated from local health care settings in Cairo, Egypt. The resistance of these MRSA towards fluoroquinolones does not depend only on mutation in target genes; other mechanisms of resistance such as the permeability effect, efflux pumps and decreased availability of quinolones at the target site can also be involved.